2001
DOI: 10.1134/1.1343548
|View full text |Cite
|
Sign up to set email alerts
|

Manifestation of nonplanarity effects and charge-transfer interactions in spectral and kinetic properties of triplet states of sterically strained octaethylporphyrins

Abstract: -Properties of the triplet states of octaethylporphyrins with the steric hindrance (free bases and Pd complexes) are studied by the methods of stationary and kinetic spectroscopy in the temperature range from 77 to 293 K. The mono-mesophenyl substitution results in a decrease in the quantum yield and shortening of the phosphorescence lifetime of Pd complexes by 250-3500 times in degassed toluene at 293 K. The phosphorescence quenching is caused by nonplanar dynamic conformations of the porphyrin macrocycle in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…This result could be explained by considering our DFT calculation given in the previous section.According to DFT calculations, dihedral angle for 1,7 positions are smaller than that of 3,5 positions. It is known that greater dihedral angle causes smaller the charge transfer due to the non-planarity of the compound[52]. This explains why 1,7 position (compound 5c) is more efficient for charge transfer than 3,5 positions (compound 5b) for the investigated compounds.…”
mentioning
confidence: 89%
“…This result could be explained by considering our DFT calculation given in the previous section.According to DFT calculations, dihedral angle for 1,7 positions are smaller than that of 3,5 positions. It is known that greater dihedral angle causes smaller the charge transfer due to the non-planarity of the compound[52]. This explains why 1,7 position (compound 5c) is more efficient for charge transfer than 3,5 positions (compound 5b) for the investigated compounds.…”
mentioning
confidence: 89%
“…It should be mentioned also that at 295 K in liquid toluene the transient T 1 → T n absorption spectra (in the region of 700−1600 nm) for sterically strained porphyrins ( meso -phenyl-substituted OEP and PdOEP) are distinguished from those measured for usual planar tetrapyrroles. , The appearance of new bands in the red and IR regions of T 1 → T n absorption spectra of sterically strained porphyrins with respect to the spectra of normal planar tetrapyrroles may be connected with the nonplanar distortion of the porphyrin macrocycle in the former molecules.…”
Section: Introductionmentioning
confidence: 98%
“…The photophysics of various expanded conjugation porphyrins have been previously investigated, and it has been demonstrated that substituents play a major role in determining porphyrin photophysical properties. For example, Vinogradov et al demonstrated that Pd-5,15-diphenyltetrabenzoporphyrin has a phosphorescence quantum yield of 0.15, whereas Pd-5,10,15,20-tetraphenyltetrabenzoporphyrin has a lower quantum yield of only 0.08 . This increased quantum yield for the disubstituted derivative originates from the more planar structure, as out-of-plane distorted porphyrins display increased nonradiative decay pathways. ,, Furthermore, Beeby et al have demonstrated an approximate doubling of solution ϕ em from 0.11 to 0.21 for 5,10,15,20-tetrasubstituted free base porphyrins when monophenyl substituents are substituted for more bulky fluorene or terphenyl substituents . Drawing from this previous work, a family of Pt-tetrabenzoporphyrins (Pt-TBPs, Figure ) incorporating 5,15-diaryl and 5,10,15,20-tetraaryl derivatives with varying substituent groups has been synthesized, and the 5,15-diaryl derivatives display a 50% enhancement in solution quantum yield as compared to the 5,10,15,20-tetraaryl derivatives .…”
Section: Introductionmentioning
confidence: 99%